Studies on banana for propagation, conservation and genome analysis - Susmita Shukla; Ritambhara Bhutani; Nibha Gupta; Shiv Kant Shukla; Taramla Raman; Mohamed A. El-Sheikh; Hosam O. Elansary; Ihab Mohamed Moussa (Cogent Food & Agriculture)
Decline in plant diversity can be ascribed to a multitude of variables encompassing human activities, climate change and exploitation of natural resources. The present study is aimed to develop robust in vitro regeneration protocol of unexplored indigenous Musa varieties (Musa acuminata var. hondakol, Musa paradisica var. sanikol, Musa paradisica var. kashkol, and Musa acuminata var. hazari) and to analyze their phylogenetic relationship. DNA barcoding using Internal Transcribed Spacer1 (ITS1) markers facilitated the molecular analysis and sequence alignment of these Musa species, which illustrated their genetic relationships. DNA sequences were submitted to the NCBI and received accession numbers. 15 days old suckers were initiated on Murashige and Skoog (MS) medium supplemented with various concentrations of phytohormones, adjuvants etc. The highest number of shoots were obtained in 6th subculturing cycle thereafter each in vitro shoot of Musa acuminata var. hazari, Musa paradisica var. kashkol, Musa paradisica var. sanikol, and Musa acuminata var. hondakol were inoculated in 1/4th MS medium supplemented with 2 mgL-1 indole-3-butyric acid (IBA) and 1 mgL-1 BAP resulted in successful rooting of 43%, 45%, 60%, and 33% respectively. The above finding showed that development effective regeneration protocol of all four varieties which can be further exploited for large scale propagation of uniform and disease-free banana plantlets.